The experiences of staff who support people with intellectual disability on issues about death, dying and bereavement: A metasynthesis. Issue 6 (12th July 2017) - Lord, Ailsa J.; Field, Stephen; Smith, Ian C.
Abstract : Background: Historically, people with intellectual disabilities have tended to be excluded from knowing about death, dying and bereavement. Staff in intellectual disability services can play a valuable role in improving understanding of these issues in those they support. This qualitative metasynthesis aimed to understand the experiences of staff supporting adults with intellectual disabilities with issues of death, dying and bereavement. Method: Thirteen papers were identified following a systematic review of six databases. Results: Three themes were developed following a lines‐of‐argument synthesis: (i) talking about death is hard: negotiating the uncertainty in death, dying and bereavement; (ii) the commitment to promoting a "good death"; and (iii) the grief behind the professional mask. "A cautious silence: The taboo of death" was an overarching theme. Conclusions: A more open culture around issues of death, dying and bereavement in intellectual disability settings is essential and could be promoted through staff training and support.